Realization of meat qualities of Black Motley bull-calves against the background of immunoprophylaxis with biological Preparations - G. Semenov, Vladimir; I. Kosyaev, Nikolay; Yu. Lavrentyev, Anatoly; A. Larionov, Gennady; V. Evdokimov, Nikolay; M. Toboyev, Gerald; A. Nikitin, Dmitry; D. Nazarov, Sergey (International Journal of Engineering and Technology, 2018)
For the first time on the basis of complex studies the zootechnical expediency of the developed biological preparations Prevention-N-A and Prevention-N-E in beef production technology for the realization of bioresource potential of meat qualities of Black Motley bull-calves was scientifically and experimentally proved. Activation of the growth and development of bull-calves in the periods of growth, rearing and fattening was established against the background of biopreparations, which resulted in higher slaughter and meat qualities of the carcasses and, as a consequence, in a higher yield of valuable cuts: brisket and sirloin by 6.1 and 4.0 kg (P < 0,01-0,001), rump by 2,6 and 1,7 kg (P
Keywords: Bull-calves; growth; rearing; fattening; biopreparations Prevention-N-A and Prevention-N-E; meat qualities.